(untitled) (قضايا سياسية, 2023)
This paper aims to shed light on the pivotal role of women in the inclusive development process which various countries- including Egypt, which tries to achieve its vision for the year 2030. It also tries to clarify the current situation with regard to the steps taken by Egypt to empower Egyptian women in different areas. Additionally, it addresses the concept of empowerment on an actual and comprehensive scale. This includes rehabilitating women and ensuring their eligibility and entitlement to leadership, unleashing their contribution in the development process as pioneers, leaders, and decision-makers, not only as women who or at the level of the assurance of the quality of the educational process.have their rights and duties yet are led by a higher manager. Instead, the real purpose and meaning of empowerment are to give women an opportunity to rule and lead. In this regard, the paper cites some pioneering models who have had the privilege of changing the course of education in Egypt in recent times whether at the educational strategy level